Aerosol Absorption: Progress Towards Global and Regional Constraints - Samset, Bjørn H. (Curr Clim Change Rep, 2018)
PURPOSE OF REVIEW: Some aerosols absorb solar radiation, altering cloud properties, atmospheric stability and circulation dynamics, and the water cycle. Here we review recent progress towards global and regional constraints on aerosol absorption from observations and modeling, considering physical properties and combined approaches crucial for understanding the total (natural and anthropogenic) influences of aerosols on the climate. RECENT FINDINGS: We emphasize developments in black carbon absorption alteration due to coating and ageing, brown carbon characterization, dust composition, absorbing aerosol above cloud, source modeling and size distributions, and validation of high-resolution modeling against a range of observations. SUMMARY: Both observations and modeling of total aerosol absorption, absorbing aerosol optical depths and single scattering albedo, as well as the vertical distribution of atmospheric absorption, still suffer from uncertainties and unknowns significant for climate applications. We offer a roadmap of developments needed to bring the field substantially forward. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40641-018-0091-4) contains supplementary material, which is available to authorized users.